Implementation of Transcatheter Aortic Valve Replacement in France - Nguyen, Virginia; Michel, Morgane; Eltchaninoff, Helene; Gilard, Martine; Dindorf, Christel; Iung, Bernard; Mossialos, Elias; Cribier, Alain; Vahanian, Alec; Chevreul, Karine; Messika-Zeitoun, David (Journal of the American College of Cardiology, 2018)
Transcatheter aortic valve replacement (TAVR) has emerged as an alternative to surgical aortic valve replacement (SAVR), but unbiased data regarding evolution of the treatment of patients with aortic stenosis at the nationwide level are scarce. This study sought to evaluate the number of aortic valve replacements (AVRs) performed in France, changes over time, and the effect of the adoption of TAVR. Based on a French administrative hospital-discharge database, the study collected all consecutive AVRs performed in France between 2007 and 2015. A total of 131,251 interventions were performed: 109,317 (83%) SAVR and 21,934 (17%) TAVR. AVR linearly increased (from 10,892 to 18,704; p for trend <0.0001) mainly due to a marked increase in TAVR (from 244 to 6,722; p for trend = 0.0004), whereas SAVR remained stable (from 10,892 to 11,982; p for trend = 0.18). Parallel to a decrease in the Charlson index (p for trend <0.05), SAVR and TAVR in-hospital mortality rates significantly declined (both p for trend <0.01). The number of TAVRs significantly increased in all age categories (<75, 75 to 79, 80 to 84, and ≥85 years of age; all p for trend = 0.003), but reached or even exceeded SAVR in the 2 oldest categories. Although mortality rates declined for both isolated SAVR and TAVR, it became similar or slightly lower for TAVR than for isolated SAVR in 2015 in the 3 oldest age categories even if it did not reach statistical significance (p = 0.66, p = 0.47, and p = 0.06, respectively). The number of AVRs markedly increased in France between 2007 and 2015 due to the wide adoption of TAVR, which represented one-third of all AVRs in 2015. Patients' profile improved, suggesting that patients are referred earlier, and in-hospital mortality declined in all AVR subsets. Despite a worse clinical profile, the immediate outcome of TAVR compared favorably to isolated SAVR in patients >75 years of age. The results may have major implications for clinical practice and policymakers.